Revisiting the North-South genetic discontinuity in Central African tree populations: the case of the low-density tree species Baillonella toxisperma - (:unkn) unknown (My University, 2020)
How the Central African rain forests have been affected by climatic fluctuations of the Quaternary remains debated. Phylogeographical studies have shown that tree species from western Central Africa often display spatially congruent genetic discontinuities, supporting the hypothesis that the forest was previously fragmented. Extensive seed dispersal is expected to accelerate the admixture between gene pools but most of the species studied so far have presumably limited seed dispersal abilities. Here, we genotyped 15 nuclear and three plastid microsatellite markers in a low-density Central African tree species with long-distance seed dispersal: Baillonella toxisperma (Sapotaceae). While plastid markers revealed a weak structure in Cameroon, nuclear markers highlighted three genetic clusters: two distributed in Cameroon and separating Atlantic coastal forests from the inland forests, and one cluster occurring in Gabon. Substantial genetic differentiation with a phylogeographical signal was detected only between Cameroonian and Gabonese populations, suggesting two major genetic clusters located approximately North and South of the equatorial climatic hinge. Genetic differentiation was very low between the clusters within Cameroon. This pattern could be partially explained by the climate niche distribution modelling applied on the Last Glacial Maximum (LGM) which predicts a unique remnant population per country. The deep North-South differentiation in a species with long-distance seed dispersal supports the hypothesis that Central African rain forests have been fragmented at the height of the equator during a substantial part of the Quaternary.
Keywords: African Research